Marine fish communities in shallow volcanic habitats. Issue 6 (30th April 2013) - Pinault, M.; Loiseau, N.; Chabanet, P.; Durville, P.; Magalon, H.; Quod, J. P.; Galzin, R.
<x xml:space="preserve">Abstract</x> This survey of the marine ichthyofauna of the Piton de La Fournaise volcano at Reunion Island is the first explanatory study of fish community structures in this area. It describes and analyses the main qualitative descriptors of the fish communities (i.e. species richness, diet, life history and geographical distribution) and their spatio‐temporal organization. This investigation in 2011 examined lava flows of different ages, including the most recent flows that entered the ocean between 1977 and 2007. In all, 263 species belonging to 45 families were observed. Overall, the fish community was notable for an absence of top predators and a predominance of opportunistic small‐bodied species, with dietary flexibility and high reproductive rates, characteristic of the early stages of ecological succession. Between‐site analysis indicated that the fish assemblages differed essentially according to the intensity of the last volcanic disturbances. Fish communities in the most disturbed sites showed the highest numbers of Serranidae and the highest proportions of omnivores and small‐bodied opportunistic carnivores, including a high proportion of endemic south‐western Indian Ocean species. The spatial pattern of this last category of species could be the result of convergent biological traits, and their adaptation to unstable environments at the expense of their competitiveness in more biodiverse, mature communities. Conversely, fish communities in the less disturbed sites showed the highest number of Holocentridae and the highest proportion of browsers of sessile invertebrates. This last characteristic could be a consequence of higher ecological maturity, illustrated by a more specialized trophic network, for assemblages in areas with less intense disturbances. Otherwise, high structural complexity, either in unconsolidated lava boulders, rocks and rubble or high coral‐covered sites, could favour the increase of the total number of species independent of disturbance intensity. Regarding the broader effects, this study helps better understand how ecosystems can resist or recover from acute disturbances and the process of ecological succession that leads to the establishment of fish communities in newly submerged habitats.